Renal assessment after pediatric living related liver transplantation - Tawhida AbdelGhaffar; Noha Mohamed; Marianne Shenouda; Ragia Said (Egyptian Liver Journal)
Abstract Background Liver transplantation (LT) has emerged as a critical intervention for pediatric patients with end-stage liver disease, significantly improving survival rates and quality of life. However, the impact of LT on renal function in this population remains underestimated. Understanding renal dysfunction post-transplant is essential, as it can complicate patient management and outcomes. Aim of the work This study aimed at evaluation of the occurrence of renal dysfunction in pediatric patients who had undergone living-related liver transplantation (LRLT) and looking into the possible risk factors. Patients and methods This was a cross-sectional cohort study estimating the occurrence of renal dysfunction among LRLT. A total of 40 patients were enrolled in the study from Dr. Yassin Abdel Ghaffar Charity Center for liver disease and research and Children’s Hospital, Ain Shams University. Children with congenital kidney disease, acute sepsis or acute gastroenteritis and dehydration at the time of the assessment were excluded. Forty age and sex matched controls were included. Reviewing medical records of the patients, history taking, and thorough physical examination were performed. Routine investigations were done for the patients. Serum cystatin C and urinary β2 microglobulin were done for patients and controls. Results The study included 40 LRLT patients, 28 males (70%) and 12 females (30%). The mean (± SD) age at transplantation was 6.84 ± 3.3 years and at the time of assessment 10.57 ± 3.8 years (ranges 1.3–13.25 years and 3–17.9 years respectively). The duration since transplantation was 4.48 ± 3.88 years (0.5–16.9 years). Serum creatinine has risen significantly after LRLT, and serum cystatin C was significantly higher in patients compared to controls. Urinary β2-microglobulin was within normal values. Though using CKD-EPI combined Cystatin C/Creatinine equation in GFR estimation increased the sector of patients falling into CKD categories significantly, none of the patients reached ESKD. Conclusion CKD is not uncommon among Pediatric LRLT. Proper estimation of GFR is crucial for effective follow up and prevention of morbidities.